Better databases for economic modelling : constructing SAMs from the SNA - Santos, Susana (2017)
Greater importance will be given to the SAM as a consistent and flexible database for economic modelling, underlining how it can support disaggregated economy-wide modelling. A proposal will be made for its construction from the SNA 93, in an ESA 95 framework.